2018
DOI: 10.1021/acsomega.8b02370
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Charges in Highly Ionic Diatomic Molecules

Abstract: Atomic charges were investigated as functions of detectable atomic and molecular constants at equilibrium structures. It was found based upon the variation idea that atomic charges in highly ionic molecules can be expressed as a function of molecular dipole moments, polarizabilities of free cations, and polarizabilities of free neutral atoms of the corresponding anions. The function can be given in the form of classical Rittner’s relationship ( J. Chem. Phys . 1951 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The electronegativity (w A , w B ) and its related asymmetric and symmetric functions together with our ionicity scales calculated by eqn ( 30)- (32), as well as the ionicity scales proposed by Philips and Pauling, 33 are listed in Tables 5 and 6 for comparison. As emphasized by Philips, 33 a reasonable scale of ionicity should be able to distinguish the coordination of crystalline A N B 8ÀN compounds.…”
Section: Ionicity Scale For Crystalline a N B 8àn Compoundsmentioning
confidence: 99%
“…The electronegativity (w A , w B ) and its related asymmetric and symmetric functions together with our ionicity scales calculated by eqn ( 30)- (32), as well as the ionicity scales proposed by Philips and Pauling, 33 are listed in Tables 5 and 6 for comparison. As emphasized by Philips, 33 a reasonable scale of ionicity should be able to distinguish the coordination of crystalline A N B 8ÀN compounds.…”
Section: Ionicity Scale For Crystalline a N B 8àn Compoundsmentioning
confidence: 99%
“…Owing to the flexibility of the electron clouds around each nucleus, the effective charge center is not at the nucleus, and the accurate dipole moments should be equal to μ = qR c , where R c is the separation between these charges [ 56 ]. Authors of [ 57 ] indicated that atomic charges in a highly ionic molecule can be computed only if the molecular dipole moment, the polarizabilities of free cations and neutral atoms of the anions, are all known. In [ 58 ], a new approach to calculating the local dipole moments and charges of atoms based on Bader’s AIM theory has been presented.…”
Section: Effective Charges Of Atomsmentioning
confidence: 99%
“…14 The exhaustive studies on spin ladder based PECs reveal a unique finding which shows that after the decimation of covalency is achieved in the purely dissociative high spin sigma state it is followed by an even higher spin state which has purely ionic bonding. 16 The persistent presence of such an ionic bonded state at a certain juncture of finding shows that in 2 nd row hetero-diatomics the negation of covalency paves the path for ionic bonding. The unique periodic trend may in turn suggest that covalency is indeed negated at a certain high spin sigma state.…”
mentioning
confidence: 99%
“…For further analysis we computed the natural bond orbital (NBO) charge analysis and we got a high negative charge density on boron and a high positive charge density on nitrogen. 16 Thus, at this extreme high state regime where all the conventional covalent bonds are broken, the polarity of the molecule is reversed with respect to the electronegativity of these atoms. Similar results are obtained when we plotted the PECs of 7 Σ + and 9 Σ + states of BeO and 5 Σ + , 7 Σ + and 9 Σ + of LiF (see Figure 4(b) and 4(c)).…”
mentioning
confidence: 99%
See 1 more Smart Citation